Regulatory Expectations of Offended Audiences: The Citizen Interest in Audience Discourse. (6th September 2017) - Das, Ranjana; Graefer, Anne
Abstract: In this article we analyze fieldwork with 90 people in the UK and Germany, exploring the expectations audiences articulate about regulatory processes behind television content they find offensive. First, mapping people's responses on to the conceptual pairing of citizens and consumers, we find audiences aligning themselves with citizen interests, even when, often on the surface, they respond to media regulation and institutions with suspicion. Second, we find that complaints that make it to media regulators are just the tip of iceberg. Third, in investigating people's expectations of actors and institutions in their responses to television content that startles, upsets, or just offends them, we note that it is crucial to treat a conversation on free speech and censorship with caution.